Agricultural innovation: an analysis of the literature - Fonseca, Maria Helena da; Picinin , Claudia Tania; Kovaleski, João Luiz (Brazilian Journal of Production Engineering, 2021)
Technology transfer is essential to boost innovation and foster the development of the agro-industrial sector, but one of the barriers encountered by farmers is the cost of technology. The objective of this research was to analyze the scientific production, indexed in the Scopus, Science Direct and Web of Science databases based on the search for the terms "technology transfer", "anthropotechnology" and "agricultural innovation *". For this, the methodology used was the Method Ordination, which consists of applying an equation to rank the most relevant articles on the researched topic, after applying a sequence of filters established by the researchers. The research did not have a time frame and there was no language delimitation for the search to be broader and the pre-defined keywords should appear in the articles, these being only for review or research, published in journals. Thus, with a formed portfolio, 16 articles were selected whose Ordination index was above 90. It can be seen that there is a need to publish more practical studies on the theme of agricultural innovation and the use of technologies by farmers.
Keywords: Anthropotechnology; technology transfer; agricultural Innovation; farmers